Acute effect of foam rolling and dynamic stretching on flexibility and jump height - Smith, J. C.; Pridgeon, B.; Hall, M. C. (The Journal of Strength and Conditioning Research, 2018)
Dynamic stretching (DS) can acutely improve vertical jump (VJ) performance but its effect lasts no more than 5 minutes. Foam rolling (FR), a form of self-myofascial release, can acutely increase range of motion (ROM) with this effect lasting less than 10 minutes. Therefore, the purpose of this study was to evaluate the time course of these effects, separately and combined, on VJ height and ROM. Twenty-nine university students completed 4 different sessions (control, FR, DS, and combo) in a randomized order. After a warm-up and baseline assessments of VJ height and sit-and-reach, participants rested (control) and performed FR, DS, and the combination of FR and DS (combo). Vertical jump height and ROM were assessed every 5 minutes for 20 minutes after treatment. Mean scores at each time point were expressed as a percent change from baseline scores. Immediately after FR, sit-and-reach was significantly greater than control (p = 0.003). Vertical jump height immediately after treatment for DS and combo was significantly greater than the control and FR counterparts (p = 0.002). Vertical jump height for DS and combo was also significantly greater than the control counterpart at 5 minutes after treatment (p < 0.001). At 15 minutes after treatment, the percent change in VJ height for the combo was significantly greater than the control counterpart (p = 0.002). Although FR has no effect on VJ performance, it can acutely increase ROM, but its effect was quickly dissipated. Foam rolling does not seem to enhance VJ height either alone or in combination with DS.